What’s Real and What’s Fake : A Study on the use of Deep Fake Technology in Advertising - Agarwal, Diya; Nath, Soma (Management Journal for Advanced Research, 2023)
According to the research "World Advertising Market: Industry Trends, Share, Size, Growth, Potential and Forecast 2021-2026" by IMARC group, the global advertising industry is anticipated to reach US$ 875 billion by the year 2026, with a predicted CAGR of 5.2% between 2021-2026. The range of digital advertisements has expanded along with the use of mobile devices and the internet. With the rise of working women and tech-savvy, career-driven millennials, higher disposable incomes, and other changes in the 21st century, advertisers and marketers now have more target groups to choose from. Due to the size of the advertising market and the rise in the volume of commercials, it is getting more and more difficult to capture them.